Social policy and social spending in Zimbabwe: 1980 to 2015 - Rekopantswe Mate (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper examines social policy in the first three decades of Zimbabwe's independence. The analysis provides answers to four sets of questions: What is the historical background of social policies in Zimbabwe and how has social spending evolved over time? What are the key institutions providing social services and what reforms have been implemented since independence? What are the outcomes in terms of service delivery, coverage rates and adequacy, as well as quality of benefits and services? How is the provision of services/social protection programmes financed? The paper concludes with reflections on lessons for social policy spending and planning. Social policy allows for the redistribution of resources, and when done fairly and transparently, social policy deepens democracy. However, Zimbabwe's experience shows that mustering national resources through prudent financial management and economic policies are important for sustainable social spending. Without resources and economic strategies, Zimbabwe's political leaders became increasingly defensive and repressive and shunned popular calls for policy change, leading the country into a developmental quagmire.
Keywords: 330